Dostoevsky at 200 - Bowers, Katherine (University of Toronto Press, 2023)
Marking the bicentenary of Dostoevsky's birth, Dostoevsky at 200: The Novel in Modernity takes the writer's art - specifically the tension between experience and formal representation - as its central theme. While many critical approaches to Dostoevsky's works are concerned with spiritual and philosophical dilemmas, this volume focuses instead on questions of design and narrative to explore Dostoevsky and the novel from a multitude of perspectives. Contributions situate Dostoevsky's formal choices of narrative, plot, genre, characterization, and the novel itself within modernity and consider how the experience of modernity led to Dostoevsky's particular engagement with form. Conceived as a forum for younger scholars working in new directions in Dostoevsky scholarship, the chapters that comprise this volume ask how narrative and genre shape Dostoevsky's works, as well as how they influence the way modernity is represented. Of interest not just to readers and scholars of Russian literature, but also to those interested in the genre of the novel more broadly, Dostoevsky at 200 is pathbreaking in its approach to the question of Dostoevsky's contribution to the novel as a form.